Composition, size distribution, length-weight relationship of sympatric mud crab species (Scylla) and the case of presumed hybrids. (5th March 2021) - Fazhan, Hanafiah; Waiho, Khor; Al-Hafiz, Ismail; Kasan, Nor Azman; Ishak, Sairatul Dahlianis; Afiqah-Aleng, Nor; Tola, Siriporn; Ikhwanuddin, Mhd
Abstract: Multiple species of mud crabs are known to co-exist sympatrically within the same ecosystem. However, little is known about the potential factors influencing their community composition. In addition, four types of presumed hybrids (SH 1–4) of the genus Scylla with distinct variations in morphological and morphometric characters were reported recently at Kota Marudu Mangrove Forest, Sabah, Malaysia. Therefore, this study described the species composition and investigated the potential species composition-regulating factors of mud crabs in Kota Marudu Mangrove Forest, Sabah, Malaysia. Further, the size distribution, length-weight relationships, and Fulton's condition factors ( K s) of Scylla species, including S. olivacea, S. tranquebarica, S. paramamosain and presumed hybrid SH 1 were also estimated and compared. Interchanging distribution patterns were observed between the two dominating species – S. paramamosain and S. tranquebarica . Interestingly, all four presumed hybrids were only found in September and October 2012. Poisson regression showed that species, sex, and sampling period were influencing factors of Scylla 's composition variation. In terms of size, S. tranquebarica was the heaviest and the largest amongst other species. Based on their length-weight relationships, females exhibited negative allometry whereas males showed positive allometry, except S. olivacea males due to their low sampling size. The K values were similar among species and sexes, except S. tranquebarica females with significantly lower mean K values. The results of this study contribute towards the understanding of the relationship between sympatric Scylla species and provide a basis for future hybrid confirmation studies. The description of length-weight relationships and K values of each Scylla species and group serves as essential baseline data for future fisheries management. Highlights: All presumed hybrids (SH 1–4) occurred together during September and October. Species, sex and month influenced Scylla 's composition variation. S. tranquebarica is the heaviest and the largest. In all species [analysed], males showed positive whereas females showed negative growth allometries.